Participatory Budgeting as if Emancipation Mattered - Baiocchi, Gianpaolo; Ganuza, Ernesto (Politics & Society, 2014)
Participatory Budgeting has by now been widely discussed, often celebr ated, and is now instituted in at least 1,500 cities worldwide. Some o f its central features—its structure of open meetings, its yearly cycl e, and its combination of deliberation and representation—are by now w ell known. In this article, however, we critically reflect on its glob al travel and argue for more careful consideration of some of its less well-known features, namely the coupling of the budgeting meetings wi th the exercise of power. We disaggregate PB into its communicative an d empowerment dimensions and argue that its empowerment dimensions hav e usually not been part of its global expansion—and this is cause for concern from the point of view of emancipation. We thus discuss the sp ecific institutional reforms associated with empowerment in the origin al version as well as its analytic dimensions. We also address some of the specific dangers of a communication-only version of PB as well as some suggestions for reintroducing empowerment.